2017
DOI: 10.1080/10691898.2017.1288556
|View full text |Cite
|
Sign up to set email alerts
|

Interpretations of Boxplots: Helping Middle School Students to Think Outside the Box

Abstract: Boxplots are statistical representations for organizing and displaying data that are relatively easy to create with a five-number summary. However, boxplots are not as easy to understand, interpret, or connect with other statistical representations of the same data. We worked at two different schools with 259 middle school students who constructed and interpreted boxplots. We observed that even students who were able to create boxplots had difficulty interpreting data represented in a boxplot. After sharing sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 9 publications
(7 reference statements)
0
5
0
6
Order By: Relevance
“…However, it is not our intention to suggest that students' development in constructing statistical graphs precedes the interpretation of statistical graphs in the overall knowledge development of data display (or vice versa). In their study on middle school students' interpretation of box plots, for example, Edwards, Özgün‐Koca, and Barr (2017) stated that
the research base cited earlier, together with our own observations of the middle school students in our study, provides ample evidence that being able to display data in a boxplot does not guarantee that one can correctly interpret a boxplot for which there is no access to the raw data. (p. 27)
…”
Section: Hypothesized Data Display Learning Progressionmentioning
confidence: 77%
“…However, it is not our intention to suggest that students' development in constructing statistical graphs precedes the interpretation of statistical graphs in the overall knowledge development of data display (or vice versa). In their study on middle school students' interpretation of box plots, for example, Edwards, Özgün‐Koca, and Barr (2017) stated that
the research base cited earlier, together with our own observations of the middle school students in our study, provides ample evidence that being able to display data in a boxplot does not guarantee that one can correctly interpret a boxplot for which there is no access to the raw data. (p. 27)
…”
Section: Hypothesized Data Display Learning Progressionmentioning
confidence: 77%
“…Entretanto, essas competências relativas ao Letramento Estatístico não se desenvolvem simplesmente por intuição. É preciso desenvolver metodologias nos espaços institucionais que promovam o trabalho pedagógico sistematizado com relação a elas, bem como às representações gráficas, de maneira tal que sejam viabilizadas as aprendizagens significativas para os alunos, referentes às estruturas de representação gráficas, ao conceito de gráfico e seus elementos e, por conseguinte, desenvolvam a compreensão deles (Curcio, 1987;Shaughnessy, 2007;Edwards et al, 2017).…”
Section: Combinação Pedagógica Entre Letramento Estatístico E Compreeunclassified
“…also asserted that partitioning a data set into quarters and thinking of the median as a measure of centre may be far less intuitive or sensible for students. Edwards et al (2017) found that only 78 (30%) of 259 middle-schoolers correctly constructed a box plot. The correct construction did not then translate into normative responses to questions such as "What percentage of data points lie above the median value/first quartile?"…”
Section: Introductionmentioning
confidence: 99%